PROSEDUR PENAGIHAN PIUTANG RAWAT INAP DAN RAWAT JALAN DENGAN MENGGUNAKAN ASURANSI DI RS PGI CIKINI - Englin Widyah Luksiana; Emerald Tobing; Melinda Malau (Fakultas Ekonomi Universitas Kristen Indonesia, 2016)
ABSTRACTThere are still many hospitals can not provide health care services properly to the public including on how the payment system is applicable. As a social unit, the hospital was faced with the scarcity of funds needed to finance their health care needs. However, the hospital is expected to provide treatment rates that are accessible by the public. The hospital also provides a delay of payment of debts to individuals, insurance and other debtor already did the contract up to the hospital in collecting receivables. Receivables have an important role in all business activities including hospitals. Accounts receivable is heading current assets whose value may affect the liquidity of a company or hospital. Collection of accounts receivable hospital carried out in accordance with the applicable procedures and prior to the maturity that has been set. If the delivery of billing claims receivable past due, then the possibility of unpaid accounts receivable hospital.Kata kunci: Prosedur, Piutang, Penagihan.